THE POTENTIAL OF SOLAR ENERGY IN THE CONDITIONS INDUSTRIAL AGGLOMERATIONS OF UKRAINE - BOYKO, SERHIY; KASATKINA, IRINA; BERIDZE, TETIANA; ZHUKOV, OLEKSIY; BOMBYK, VADYM (Herald of Khmelnytskyi National University. Technical sciences, 2023)
In Ukraine, the largest agglomeration of mineral development is the Kryvyi Rih iron ore basin, which includes a large number of mining enterprises. Meanwhile, the harmful impact on the environment of mining enterprises is very significant and primarily causes the disturbance of fertile lands suitable for use in agriculture. It should be noted that mining enterprises are significant consumers of electricity, which currently has certain limitations in its consumption and, taking into account the actual consumption and the given limits of maximum energy consumption, it is currently in deficit both in the Dnipropetrovsk region and in Ukraine. In recent years, solar energy has been actively developing in Ukraine. The issue of the introduction of solar power plants in the conditions of industrial agglomerations on the territory of Ukraine is relevant not only among the scientific community, but also among industrial enterprises. For the problem under investigation, it is logical and expedient to study and analyze the relevant indicators of weather conditions. Thus, analytical and quantitative predictive values of seasonality indices and peak hours of solar irradiation were obtained. The application of the obtained calculations allows determining the optimality of the application of the proposed devices of solar power plants to obtain the maximum possible value of the generated power for the given conditions. A positive driver in this direction is also the fact of using the spaces of decommissioned territories and active industrial agglomerations for energy production in an environmentally safe way.